Dojrzali nauczyciele o swojej pracy – raport z badań - Elżbieta Strutyńska (Studia z Teorii Wychowania)
The article outlines how mature teachers perceive the strengths and challenges in everyday schoolwork. The presented analyzes are based on 14 individual in-depth interviews (IDI) with teachers who have many years of work experience in school (minimum 20) and are over 50 years old. In the research, I used thematic analysis. In addition, I coded the data using the inductive approach. I selected four categories of thematic threads that define the advantages of a mature teacher. The respondents described themselves not only through the prism of individual characteristics but also through various types of competencies (e.g. didactic and methodological), the ethos of the profession and the specificity of the period of life. At the same time, they pointed to the difficulties associated with many years of work in the domain - health problems, contemporary challenges and many years of professional experience.